Natural life cycle of Versteria cuja (Taeniidae) in Argentina and histopathology of metacestodiasis in intermediate hosts - Estefanía Bagnato; Francisco Acuña; Federico Brook; Gabriel Mario Martin; Claudio Gustavo Barbeito; María Celina Digiani (Parasitology, 2023)
Using morphological and molecular studies, the life cycle of Versteria cuja (Cestoda: Taeniidae) was elucidated, involving subterranean rodents (Ctenomyidae) as intermediate hosts, and the lesser grison, Galictis cuja (Mustelidae), as definitive host. Metacestodes (cysticerci and polycephalic larvae) were found mainly in the liver but also in spleen, pancreas, lungs and small intestine of 2 species of tuco-tucos (Ctenomys spp.) from Chubut, Argentina. Identity of the metacestodes with the adult was based primarily on the number, size and shape of rostellar hooks: 40–48 hooks in 2 rows, particularly small (10–16 μm total length by 6–10 μm wide), composed of handle, blade and guard with characteristic shapes. Genetic analysis (cox1 gen mtDNA) performed on metacestodes from both intermediate hosts corroborated their conspecificity with adults of V. cuja from lesser grisons in the same locality. Histopathological study showed the hepatic parenchyma altered by the presence of cysts containing larvae, each surrounded by a capsule of connective tissue with inflammatory infiltrate, atrophied hepatocytes and an increase of bile ducts. In the lung, in addition to the cysts, dilated alveoli, oedema and hyperaemic blood vessels were observed. This is the first report of a natural life cycle of a Versteria species from South America. It shows strong similarities with that described for a North American zoonotic lineage of Versteria, confirming a close relationship between V. cuja and this North American lineage, as previously demonstrated by molecular studies. Consequently, the zoonotic potential of V. cuja should not be disregarded.